Medical terminology of patients’ medical cases: structural and semantic analysis - M. I. Andreeva; R. R. Shaekhova (Вестник Самарского университета: История, педагогика, филология)
The research focuses on the pivotal issue of human-related nominations of medical terminology. The scrutiny is given to the terminology of patients’ medical cases and complete management. The work attempts to fill in the research niche of structural, semantic analysis and specifics of interlinguistic equivalents of English and Russian medical terminology of patient cases. The nominations of human body, conditions, triggers and medical manipulations are studied. The research material, followed methods and approaches contribute to the research relevance implemented within human-oriented paradigm. The study aims at clarifying and specifying the semantic and structural features of medical terms elicited from the subcorpora of patient cases presented in the ‘House M.D.’ TV series, compiled by the authors. The aim is achieved through the study of semantic components, contextual features, lexical valency and derivational features of 168 terms. The corpora-based approach combined with text proces sing tools and techniques used by the authors make the research novel. Moreover, the developed algorithm provides a solid base for further investigations alike. The research was implemented in four stages. The word frequency analysis of the words in the compiled corpora showed the prevalence of medical terms. The number of terminological word combinations equals to one-word terms. Among the former word combinations with prepositions are not frequent. The latter exhibit clear derivational patterns with a marked set of word formation suffixes. The distribution of the terms into semantic groups revealed the prevalence of the semes ‘diagnosis’, ‘symptoms’ and ‘pathology’. The need for transliteration of English-Russian equivalents of medical terms arises due to the Latin origin of the most part of the terms which may be regarded as international medical vocabulary.